The Role of Good Corporate Governance in Practice Tax Avoidance: Analysis Independent Commissioner, Capital Intensity, CEO, and Audit Quality on Sector Properties and Real Estate (2019-2023) - Azis Nurdiansyah; Yuni Putri Yustisi (UNIVED Press, 2025)
This study aims to examine the impact of independent commissioners, capital intensity, CEOs, and audit quality on tax avoidance practices in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Tax avoidance was measured using the Effective Tax Rate (ETR), while data were collected from annual financial reports and analyzed using multiple linear regression. The results reveal that independent commissioners and capital intensity have a significant negative effect on tax avoidance, indicating that the presence of independent commissioners and a high proportion of fixed assets in a company can reduce tax avoidance efforts. On the other hand, while CEOs and audit quality were statistically significant, they did not align with the initial hypotheses, thus failing to support them. These findings confirm that corporate governance and fixed asset composition play crucial roles in minimizing tax avoidance. This research is expected to serve as a reference for policymakers, business practitioners, and future researchers in understanding and addressing tax avoidance issues in Indonesia